2023
DOI: 10.17533/udea.vitae.v30n1a351486
|View full text |Cite
|
Sign up to set email alerts
|

Study of total antioxidant capacity of red raspberry (Rubus idaeous L.) shoots

Abstract: BACKGROUND: Today, cardiovascular, oncological, and neurodegenerative diseases are the main causes of death in the world, according to official World Health Organization (WHO) statistics. Antioxidants are used to treat and prevent these diseases. In order to develop optimal technology for obtaining drugs based on plant extracts with antioxidant action, it is necessary to determine the total antioxidant capacity of raspberry shoots.OBJECTIVES: The study aimed to determine the total antioxidant capacity of red r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In our studies, it was found that green tea leaf is rich in catechins (epigallocatechin3Ogallate, epicatechin, (+)catechin), flavonols (rutin, quercetin), organic (citric, oxalic acid) and phenylcarboxylic acids (gallic, quinic and caffeic acid) [6,7]. The main group of compounds in green tea leaf are catechins that have antioxidant, anti-inflammatory, antimicrobial, and antifungal effects [8,9].…”
Section: Original Researchmentioning
confidence: 90%
“…In our studies, it was found that green tea leaf is rich in catechins (epigallocatechin3Ogallate, epicatechin, (+)catechin), flavonols (rutin, quercetin), organic (citric, oxalic acid) and phenylcarboxylic acids (gallic, quinic and caffeic acid) [6,7]. The main group of compounds in green tea leaf are catechins that have antioxidant, anti-inflammatory, antimicrobial, and antifungal effects [8,9].…”
Section: Original Researchmentioning
confidence: 90%
“…In many chronic diseases such as diabetes mellitus, hypertension, atherosclerosis, Alzheimer's disease, and cancer [1], inflammation and oxidative stress invariably play pivotal roles. During the inflammatory response, neutrophils and macrophages generate substantial quantities of free radicals to combat and eliminate foreign invaders [2,3]. Furthermore, recent research has revealed that non-phagocytic cells, like interleukin-6 (IL-6), can also produce free radicals by expressing NADPH oxidase [4].…”
Section: Introductionmentioning
confidence: 99%
“…The human body has its own antioxidant system, which consists of the following enzymes: superoxide dismutase, catalase, and glutathione peroxidase [5,6]. However, due to endogenous or exogenous influences, the antioxidant system is not always able to completely inactivate free radicals, thereby increasing the risk of developing the diseases above.…”
mentioning
confidence: 99%